The inhibition of potential pathogens by persimmon puree and selected phenolics - Weber, Casey Grant (Kansas State University, 2009)
Three experiments were conducted to study the antimicrobial effectiveness of persimmon puree and phenolic compounds commonly found in the persimmon and plum. The objectives in experiment 1 were to evaluate the antimicrobial effects of persimmon puree on BioballTM Listeria monocytogenes and Escherichia coli O157 in a liquid medium. Persimmon puree was added at 1, 3, 5, and 10% wt./vol concentrations to brain heart infusion broth and inoculated with BioballTM Listeria monoctogenes and BioballTM Escherichia coli 0157. Microbial growth was evaluated at 0, 24, 36 and 72 h. Results indicated that at 24 h, persimmon puree at all concentrations suppressed (P<0.05) growth of L. monocytogenes compared to the control. Suppressed (P<0.05) growth of L. monocytogenes continued through 36 and 72 h for all concentrations of persimmon puree tested. However, due to non-pathogenic background Gram-negative micoflora, inhibition of E. coli O157 could not be ascertained. The objectives of experiment 2 were to evaluate the antimicrobial effectiveness of selected phenolic compounds (benzoic acid, gallic acid, vanillic acid, chlorogenic acid, and quercetin on E. coli O157:H7, Salmonella Typhimurium, Bacillus cereus, Yersinia enterocolitica, L. monocytogenes, and Staphylococcus aureus. Quercetin, vanillic, and chlorogenic acids were effective against selected pathogens at varying levels, but not as potent as Benzoic or Gallic acid. Results indicated that benzoic acid had the most effect against E. coli O157:H7, S. Typhimurium and B. cereus at concentrations of 452.98, 239.63 and 518.79 µg/ml, respectively. Gallic acid was the most effective against Y. enterocolitica, L. monocytogenes, and S. aureus at concentrations of 11.01, 29.06 and 22.45 µg/ml, respectively. The objective of experiment 3 were to evaluate the antimicrobial effectiveness of persimmon puree at concentrations of 0, 3, 5 and 10% wt./wt on a five strain cocktail of L. monocytogenes in ground beef. There was no suppression of growth at any concentration at 0, 1, 3 or 5 d. However, there was an increase (P<0.05) on 5 d for concentrations 5 and 10% persimmon puree when compared to the control. These series of experiments suggest that benzoic and gallic acids may have potential to suppress microbial growth. Persimmon puree appears to be an effective antimicrobial agent against Gram-positive bacteria in a liquid medium. However, incorporation of persimmon puree into ground beef did not yield an antimicrobial effect. Therefore, more research needs to be conducted to validate the effectiveness of phenolic compounds and persimmon puree as antimicrobial agents in food substances.
Keywords: Phenolic; Persimmon; Antioxidants; Antimicrobial; Pathogens; Agriculture, Food Science and Technology (0359)